Learning Process Using WhatsApp Media: Effectiveness Analysis Makes Agreements in the Group Learning Process - Erik Saut H Hutahaean; Rini Indryawati; Maria Chrisnatalia (International Conference of Mental Health, Neuroscience, and Cyber-psychology)
Technology is an effective means to facilitate the learning communication process, but there are still many people who are familiar with the process of direct communication. This study intends to analyze the effectiveness of using WhatsApp in carrying out tasks. Three students were involved in a simple experiments, the task was to make an agreement on the list of important items brought. The data obtained are in the form of communication transactions that occur during discussions. This study found a low score in making decisions about the order of items that were important to be carried, and there was a discussion over the time limit. Another results show that there are conversations that are not balanced and not relevant to their purpose. One dominates the other two passive, there is a chat that is not in line with the direction of discussion.